Penerapan Permainan Tebak Gerakan Seru bagi Anak Usia Dini dengan Hambatan Pendengaran - Anisa K. Aini; Lisdwanti Lisdwanti; Itriani Daeng Tjenu; Pupung Puspa Ardini; Fitriana A. Salila; Nur Fajrina Kilapong; Tirsa Tangia (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
arly childhood learners with hearing impairment have limitations in receiving verbal information; therefore, they need learning activities that emphasize visual aspects, movement, and direct interaction. This study aims to describe the implementation of the Fun Motion Guessing game for early childhood learners with hearing impairment. This research used a descriptive qualitative approach. Data were collected through observation, documentation, and field notes during the game activity. The game was conducted using picture cards containing simple activities, and children were asked to demonstrate movements based on the pictures without using verbal communication. Other children were guided to guess the demonstrated movements through visual observation. The findings show that the Fun Motion Guessing game helped children become more active in learning, understand visual instructions, express themselves through body movements and facial expressions, and interact with peers. This activity also encouraged children’s courage, concentration, cooperation, and self-confidence during the learning process. Therefore, the Fun Motion Guessing game can be used as an alternative enjoyable learning activity that is appropriate for the characteristics of early childhood learners with hearing impairment.